Hybrid coating of alginate microbeads based on protein-biopolymer multilayers for encapsulation of probiotics - Falco, Cigdem Yucel; Amadei, Federico; Dhayal, Surender K.; Cárdenas, Marité; Tanaka, Motomu; Risbo, Jens (Biotechnology progress, 2019)
A hybrid coating based on multilayers of proteins and biopolymers was developed to enhance the protection performance of alginate microbeads against acidic conditions for delivery of probiotics (Lactobacillus rhamnosus GG). Zeta potential measurements and quartz crystal microbalance with dissipation confirmed layer-by-layer deposition of protein-polymer layers. The stability of protein-based coatings during simulated gastric fluid (SGF) treatment was monitored by microscopy. Protein-coated microbeads were partially dismantled, whereas polymer-coated microbeads were intact after a sequential treatment in simulated gastric and intestinal fluids. This suggests that hybrid formulation offers an advantage over the coatings based on biopolymer multilayers in terms of better release of bacteria. Uncoated alginate microbeads completely dissolved and could not protect bacteria after SGF treatment whereas microbeads with hybrid coating showed increased physical stability and a modest decrease of culturability of 3.8 log units. Therefore, this work provides a concept for future protein-based hybrid coatings for bacterial delivery systems.